Feeling close to a Crab-Thing in virtual reality: Does avatar appearance always matter in forming meaningful connections? A case study - Agnew, Christopher R. (Frontiers in Virtual Reality, 2022)
Recent experimental research revealed that people can form meaningful relationships interacting with strangers in virtual reality (VR), with resulting affiliative outcomes (e.g., feelings of closeness) at the same levels as those attained via interactions in other sensory-rich communication modalities. The present preregistered experiment examined whether avatar type and avatar matching in VR influence levels of closeness (and affiliated constructs) generated among previously unacquainted strangers using a validated structured discussion procedure. Based on previous theory and research, we hypothesized that affiliative outcomes would not differ (1) regardless of whether the interacting avatars appeared to be human or not, and (2) regardless of whether there was a (mis)match in avatar type between interactants. Two hundred and four previously unacquainted undergraduate students were randomly assigned to interact in VR as pairs in one of three stylized avatar conditions: both human in appearance, both non-human in appearance (Crab-Things, created for this study), or one human and one Crab-Thing. Results were consistent with hypotheses, suggesting that closeness and related outcomes can be generated and experienced in VR regardless of the stylized avatar types used in the current study. Exploratory analyses of individual difference variables (personality and attachment) as possible moderators of stylized avatar type effects yielded non-significant findings, supporting the generalizability of findings across key intra- and interpersonal dispositions.